Biosorption of Cr(VI) from aqueous solution using agricultural wastes, with artificial intelligence approach. Issue 3 (11th February 2016) - Fawzy, Manal; Nasr, Mahmoud; Abdel-Gaber, Ashraf; Fadly, Shaimaa
ABSTRACT: Removal of Cr(VI) from aqueous solution by date-palm-leaves (DPL) and broad-bean-shoots (BBS) was investigated. FTIR, SEM, and EDAX showed that DPL has higher ability for ion-exchange to remove Cr(VI). Langmuir and Freundlich adsorption isotherms and kinetics revealed that DPL exhibited higher biosorption capacity. At Cr(VI) 100 mg/L, biosorbent-dose 5 g/L and 60 min contact-time, maximum Cr(VI) removal for DPL (98%) and BBS (95%) was achieved at pH 2 and 1, respectively. Adaptive-neuro fuzzy inference system determined the most important factor affecting Cr(VI) removal. The model indicated that DPL is more tolerant to pH levels, while BBS is a pH-sensitive adsorbent.